Breaking the clean room barrier: exploring low-cost alternatives for microfluidic devices - Rodríguez, Cristian F.; Andrade-Pérez, Valentina; Vargas, María Camila; Mantilla-Orozco, Andrés; Osma, Johann F.; Reyes, Luis H.; Cruz, Juan C. (Frontiers in Bioengineering and Biotechnology, 2023)
Microfluidics is an interdisciplinary field that encompasses both science and engineering, which aims to design and fabricate devices capable of manipulating extremely low volumes of fluids on a microscale level. The central objective of microfluidics is to provide high precision and accuracy while using minimal reagents and equipment. The benefits of this approach include greater control over experimental conditions, faster analysis, and improved experimental reproducibility. Microfluidic devices, also known as labs-on-a-chip (LOCs), have emerged as potential instruments for optimizing operations and decreasing costs in various of industries, including pharmaceutical, medical, food, and cosmetics. However, the high price of conventional prototypes for LOCs devices, generated in clean room facilities, has increased the demand for inexpensive alternatives. Polymers, paper, and hydrogels are some of the materials that can be utilized to create the inexpensive microfluidic devices covered in this article. In addition, we highlighted different manufacturing techniques, such as soft lithography, laser plotting, and 3D printing, that are suitable for creating LOCs. The selection of materials and fabrication techniques will depend on the specific requirements and applications of each individual LOC. This article aims to provide a comprehensive overview of the numerous alternatives for the development of low-cost LOCs to service industries such as pharmaceuticals, chemicals, food, and biomedicine.